SPECIMEN HOLDER FOR VIRTUAL WELDING - SHIN, SANG HO; KIM, MAENG NAM; LEE, DONG YOUP (2016)
The present invention relates to a specimen holder for virtual welding which easily fixates a parent metal at a desired height and a desired angle during a virtual welding training. The specimen holder of the present invention comprises: a base; a vertical frame placed vertically on top of the base; an arm frame placed vertically on one side of the vertical frame; an elevating unit to fixate the arm frame in a position of the vertical frame moved vertically; an arm installed for each set angle on an end unit of the arm frame; a parent metal for attachment and detachment training from the end of the arm; a base sensor placed in the arm to measure a position of the arm; and a control unit to detect a position of the parent metal for training during a virtual welding training with the value measured by the base sensor as a standard. 본 발명은 가상 용접 훈련시 모재를 원하는 높이와 원하는 각도에 손쉽게 고정시킬 수 있는 가상 용접용 시편 거치대에 관한 것이다. 본 발명은 베이스; 상기 베이스 상측에 수직하게 구비된 수직 프레임; 상기 수직 프레임의 일측에 수직하게 구비되는 암 프레임; 상기 암 프레임을 상기 수직 프레임의 상하 방향으로 이동된 위치에 고정시키는 승강부; 상기 암 프레임의 단부에 설정 각도 별로 설치되는 암; 상기 암의 끝단에 탈착되는 훈련용 모재; 상기 암의 내부에 구비되고, 상기 암의 위치를 측정하는 베이스 센서; 및 상기 베이스 센서에서 측정된 값을 기준으로 가상 용접 훈련 시에 상기 훈련용 모재의 위치를 감지하는 제어부;를 포함하는 가상 용접용 시편 거치대를 제공한다.